CLINICAL CASE OF USING TOCILIZUMAB FOR A FEMALE PATIENT WITH AN EARLY DEBUT OF SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS - О. L. Lomakina; Ye. I. Alekseyeva; S. I. Valieva; Т. М. Bzarova; R. V. Denisova; Т. V. Sleptsova (Вопросы современной педиатрии)
The article describes a case of an early debut and difficult treatment of systemic juvenile idiopathic arthritis resistant to peroral glucocorticoids. The described clinical example demonstrates the successful use of tocilizumab, a monoclonal antibody drug, against interleukin-6 receptors. After the 1st drug infusion the systemic manifestations of the disease were alleviated, by the 6th week of the tocilizumab treatment inflammatory changes in the joints were reduced, and by the 16th week the inactive stage of the disease was registered, which made it possible to stop the administration of glucocorticoids per os. Duration of remission of articular syndrome and extra-articular manifestations was 10 months.